Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.17100/nevbiltek.696744
|View full text |Cite
|
Sign up to set email alerts
|

Halk Sağlığı Uygulamalarının Enterobius Vermicularis’in Korunma ve Kontrolündeki Önemi

Abstract: ÖzEnterobius vermicularis; dünyada ve ülkemizde ilkokul çağı çocuklarda ilk sıralarda görülen parazitler arasındadır. Bu parazit; yayılmasında sosyoekonomik durum, kişisel hijyen alışkanlıkları, çevre ve alt yapının iyileştirilmesi gibi etkenlerin önemli olması ve önlenebilir olması nedeniyle önemli bir halk sağlığı sorunudur. Ayrıca bu parazitin çocuklar üzerinde; ülser, egzama, karın ağrısı, anemi, uyku sorunları gibi sağlık sorunları ile doğrudan ve akademik başarısızlık, okul devamsızlığı gibi sorunlarla d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Appendectomy alone is not an adequate treatment for patients whose appendectomies are found to contain E. vermicularis since surgery cannot eliminate the cause and will result in only one condition, anti-helminthic drugs should be recommended to patients after surgery (14,18). In conclusion, it is reported that inflammatory changes are rare in cases where parasite is detected in the appendix lumen (5,10). In our study, the presence of E. vermicularis causes acute inflammation of the appendix lumen.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Appendectomy alone is not an adequate treatment for patients whose appendectomies are found to contain E. vermicularis since surgery cannot eliminate the cause and will result in only one condition, anti-helminthic drugs should be recommended to patients after surgery (14,18). In conclusion, it is reported that inflammatory changes are rare in cases where parasite is detected in the appendix lumen (5,10). In our study, the presence of E. vermicularis causes acute inflammation of the appendix lumen.…”
Section: Discussionmentioning
confidence: 59%
“…Enterobius vermicularis (E. vermicularis) is the most common human parasite. E. vermicularis is both the most common parasitic agent in the gastrointestinal tract and the most common cause of gastrointestinal infection worldwide and it also causes appendicitis among parasitic diseases (5,6). E. vermicularis is an intestinal parasite that is located in the last part of the small intestine, the first part of the cecum and colon, which is more common in the cold climate regions of the underdeveloped countries and frequently affects children (1,4).…”
Section: Introductionmentioning
confidence: 99%